2019
DOI: 10.1097/md.0000000000016938
|View full text |Cite
|
Sign up to set email alerts
|

Impaired heart rate recovery as a predictor for poor health-related quality in patients with transient ischemic attack

Abstract: We aimed to investigate heart rate recovery (HRR) in patients with transient ischemic attack (TIA) and the relationship between HRR and health-related quality of life (HRQOL). All available patients were enrolled during the enrollment period. A total of 120 patients with TIA and 120 healthy controls were included in this study. A treadmill stress test was performed to calculate the HRR. The HRR were calculated as follows: HRR 1, 2, 3, and 5 minutes = heart rate at peak during exercise − heart rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Few studies have examined heart rate recovery in individuals with stroke, none of which have examined recovery to this length of time post-exercise. In individuals with TIA, Li et al (2019) found that heart rate recovery was impaired at 5-min post-exercise (54 ± 16 bpm) compared to control subjects without a history of TIA (73 ± 15 bpm), at levels indicative of autonomic dysfunction. Our sample produced heart rate recovery values at 5 min postexercise (58 ± 23 bpm) that were very similar their findings (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Few studies have examined heart rate recovery in individuals with stroke, none of which have examined recovery to this length of time post-exercise. In individuals with TIA, Li et al (2019) found that heart rate recovery was impaired at 5-min post-exercise (54 ± 16 bpm) compared to control subjects without a history of TIA (73 ± 15 bpm), at levels indicative of autonomic dysfunction. Our sample produced heart rate recovery values at 5 min postexercise (58 ± 23 bpm) that were very similar their findings (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…In individuals with TIA, Li et al (2019) found that heart rate recovery was impaired at 5-min post-exercise (54 ± 16 bpm) compared to control subjects without a history of TIA (73 ± 15 bpm), at levels indicative of autonomic dysfunction. Our sample produced heart rate recovery values at 5 min postexercise (58 ± 23 bpm) that were very similar their findings (Li et al, 2019). The sustained elevations of cfPWV and impaired heart rate recovery may be yet another indicator of autonomic imbalances in this population, especially after exercise.…”
Section: Discussionmentioning
confidence: 93%
“…HRR abnormalities are often seen in patients with metabolic disorders, including cardiovascular disease, fatty liver, diabetes and prehypertension [4][5][6][7][8]. Blunted HRR has been reported the association with chronic heart failure and new-onset atrial fibrillation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…HRR abnormalities are often seen in patients with metabolic disorders, including cardiovascular disease, fatty liver, diabetes and prehypertension [4][5][6][7][8]. Blunted HRR has been reported the association with chronic heart failure and new-onset atrial fibrillation [9,10].…”
Section: Introductionmentioning
confidence: 99%